DATA-DRIVEN BUDGET OPTIMIZATION FOR JOB CREATION IN NIGERIA USING THE SIMPLEX METHOD - Joseph, Hope Eyikojonwa; Omolehin, Joseph Olorunju; Momoh, Sheidu Omeiza (FUDMA JOURNAL OF SCIENCES, 2025)
Unemployment remains a core issue in Nigeria, undermining economic stability, social welfare, national development and security. Addressing the issue requires visionary and evidence-based interventions to optimize the use of existing resources. This study examines how Nigeria’s 2024 budget of ₦27.5 trillion can be strategically utilized to optimize job creation. using the Simplex technique, a quantitative optimization method. This research presents the optimal distribution of resources across key sectors for the purpose to attain maximal employment levels. The research concentrates on five key sectors prioritized in the 2024 budget are Education, Healthcare, Infrastructure, Security and Defense, and Social Development. The ranking of these is based on their employment coefficients, which measure the number of jobs created for every billion Naira of expenditure. Preliminary findings revealed that the budget allocations can generate approximately 400,600 jobs.